Parametric studies and reliability of near-wall turbulence modeling for Large Eddy Simulation of incompressible flows / Khan Raqib Mahmud, M. M. Rhaman and Abul Kalam Al Azad - Mahmud, Khan Raqib; M. M., Rhaman; Al Azad, Abul Kalam (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
We present the parametric studies of near-wall turbulence modeling for Large Eddy Simulation (LES) of incompressible flows. Flow across a step channel is considered for the numerical studies as the complex wall bounded flows can be highly sensitive to the friction enforced and results are analyzed according to the physics of the flow. We apply the wall shear stress model to model the boundary layers in LES which we refer to as near-wall turbulence modeling. This paper is mainly concerned with the investigation of sensitivity of friction parameter of wall shear stress model and the reliability of near-wall turbulence modeling for LES of incompressible flows. The accuracy and efficiency of LES with near-wall turbulence modeling for complex turbulent flows are investigated by the parametric studies of model parameters. It is observed that wall shear stress model computes the reattachment length for flows in a step channel for both constant and parabolic inflow profile efficiently and with high accuracy compared with other results.